APPENDIX 3A Ethical Considerations When Altering Digital Images. Issue 11 (2nd November 2015) - Gallagher, Sean R.; Neuman, Joseph
Abstract : The ubiquitous use of digital imaging has greatly simplified and accelerated life science research. However, the ease of manipulating digital images also presents serious ethical issues. This unit presents guidelines and cautions describing best practices for use, analysis, and presentation of digital image data. © 2015 by John Wiley & Sons, Inc.